آراء العاملين في المؤسسات الحكومية حول أهمية الأتمتة وفوائدها - حمشو, ميساء; عـباس, فداء (Latakia University Journal - Economic and Legal Sciences Series, 2019)
أجريت دراسة ميدانية لمعرفة آراء العاملين في المؤسسات الحكومية حول أهمية الأتمتة والفوائد التي يمكن الحصول عليها عند تطبيق الأتمتة في مديرية المالية في محافظة دمشق. ومن خلال تحليل الاستمارة التي تم توزيعها على العاملين توصلنا إلى أن الخبرة والمهارة التي يملكها الموظف في استخدامه للحاسوب تلعب الدور الرئيسي في تشجيع وتطبيق الأتمتة في المؤسسة أكثر من نوعية الشهادة التي يحملها الموظف، وكذلك لا تلعب مدة خدمة الموظف دورا في مدى تفضيل الموظف للتعامل مع الحاسوب، كما توصلنا إلى أن العمل اليدوي يكمل ويتمم العمل المؤتمت ولا يمكن إلغاء أحدهما إذا أردنا نجاح أعمال المؤسسة نجاحاً تاماً ، ولوحظ أيضاً أنه عند تطبيق الأتمتة تواجه المؤسسة بعض الصعوبات التي لا يجب الاستهانة بها ويجب أخذها بعين الاعتبار من أجل الحصول على الفوائد المرجوة من تطبيق الأتمتة في المؤسسة وعلى ضوء الصعوبات والنتائج تم اقتراح عدة مقترحات للاستفادة منها من قبل صانعي القرار . A field study was carried out to know the opinions of the workers about the importance of automation and the possible benefits obtained when automation is applied in the Financial Directory at Damascus Governory. From the analysis of questionnaire distributed to the workers, we concluded that computer skills and the experience of the workers play the principle role in encouraging the implementation of automation in the institution rather than the certificates of the workers, and that the employment period of the employees does not play any role in preferring the work with computer. We also found that manual work completes automation work and that it is impossible to delete anyone of them if we want to have successful work in the institutions. It was also observed that some difficulties face that institution during automation implementation which must not be neglected and must be taken into consideration in order to get the hoped benefits from it in the institution. According to results and difficulties, some suggestions were made to the decision markers to make use of.